Negotiation Decision Support Systems: Analysing Negotiations Under the Conditions of Risk - Agarwal , Nipun (Journal of Law and Governance, 2009)
Negotiation Theory is a research area with emphasis from three different research streams being game theory, psychology and negotiation analysis. Recently, negotiation theory research has moved towards the combination of game theory and psychology negotiation theory models that could be called Integrated Negotiation Theory (INT). As, negotiations are often impacted by external factors, there is risk associated with achieving the expected outcomes. Prospect theory and Negotiation theory are combined in this paper to incorporate the risk associated within negotiations. Negotiation Decision Support Systems (NDSS) is an information technology tool using negotiation theory and artificial intelligence to assist disputants in a negotiation to obtain better negotiated outcomes than they can obtain otherwise. Due primarily to the limitations of bounded rationality and differing mental or physical state of the disputant. In the past, NDSS have primarily used game theory within their negotiation and decision making framework to assist disputants resolve negotiations, as game theory is easier to incorporate. This paper shows how INT and Risk Factors (Prospect Theory) can be incorporated into an NDSS to improve negotiation decision making.